Ugly Doll - Miller, Dani (Cornfield Review, 2018)
For an assignment, we had to think back to a memory that was before we were 10 years old. The language we used in the stories had to reflect that of the age the memory took place. I can't remember the exact age I chose for the assignment, but I want to say around 8-10 years old.